Diagnostic accuracy of home sleep apnea testing using peripheral arterial tonometry for sleep apnea: A systematic review and meta‐analysis. (6th July 2022) - Ichikawa, Masahiro; Akiyama, Tomoaki; Tsujimoto, Yasushi; Anan, Keisuke; Yamakawa, Tadashi; Terauchi, Yasuo
Summary: This study aimed to evaluate the diagnostic accuracy of home sleep apnea testing using peripheral arterial tonometry for sleep apnea as an alternative to polysomnography. We conducted a systematic review and meta‐analysis of observational studies, randomized controlled trials, and diagnostic case–control studies examining the diagnostic accuracy of peripheral arterial tonometry by searching the CENTRAL, MEDLINE, EMBASE, ICTRP and ClinicalTrials.gov databases on 5 October 2021. We assessed the risk of bias of the included studies using the Quality Assessment of Diagnostic Accuracy Studies‐2 tool. A bivariate random‐effects model was generated to derive the summary point estimates of sensitivity and specificity with 95% confidence intervals at different apnea–hypopnea index cutoffs. This meta‐analysis included 13 studies (1227 participants, median prevalence of sleep apnea with apnea–hypopnea index ≥ 5 events per hr: 85%). The risk of bias in the included studies was low to moderate. The pooled sensitivity and specificity estimates were 96% (95% confidence interval: 93%–97%) and 44% (95% confidence interval: 32%–56%) at apnea–hypopnea index ≥ 5 events per hr, 88% (85%–91%) and 74% (63%–83%) at apnea–hypopnea index ≧ 15 events per hr, and 80% (66%–89%) and 90% (83%–95%) at apnea–hypopnea index ≧ 30 events per hr, respectively. Peripheral arterial tonometry resulted in a significant number of false negatives and false positives at any apnea–hypopnea index cutoff when applied to the median prevalence setting of the included studies. The inadequate sensitivity and specificity of peripheral arterial tonometry render it an unsuitable alternative to polysomnography for detecting sleep apnea for apnea–hypopnea index ≧ 5, 15 and 30 events per hr.